First Year at University: Perceptions and Experiences of Students - Holdaway, Edward A.; Kelloway, Karen R. (Canadian Journal of Higher Education, 1987)
This study was initiated by concerns in the literature over freshman students and by the need to know more about students' perceptions of their university experience. In 1984, all 937 first-year students in the Faculties of Arts, Business, Education, Engineering, and Science who had come directly to the University of Alberta from high school were asked about their university experiences and the transition from high school. Family members, the University's reputation, and the University's proximity exerted the greatest influence upon the decision to attend. Preparation for an interesting career, obtaining a well-paying job, and learning about topics of special interest were the most important goals associated with their programs. Students considered that they were best prepared in reading skills, listening skills, and taking notes, and least well prepared in budgeting time, library skills, and study skills. Most assessed that they were working considerably harder than at high school, and many said that high school had not adequately prepared them for university. The greatest need to adjust occurred in amount of work, stress, difficulty of work, and methods of instruction. Students varied considerably in the extent to which their expectations were met and the time taken to feel "at ease."